Factors Influencing Taxpayers’ Willingness to Participate in Voluntary Disclosure Program - Rifki Inderawan, Ahmad; Prihatiningtias, Yeney Widya (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to examine the influence of knowledge of voluntary disclosure program, tax sanctions, and subjective norms on taxpayers’ willingness to participate in voluntary disclosure program. Respondents in this study amounted to 100 Individual Taxpayers registered at KPP Pratama Banyuwangi and were collected using the survey method with a questionnaire instrument and the sample was determined using the purposive sampling method. The analytical method used was multiple regression analysis to test the effect by using the t test through the SPSS application. The results of this study indicate that the knowledge of voluntary disclosure program, tax sanctions, and subjective norm variables positively influence taxpayers’ willingness to participate in voluntary disclosure program.